Surface Subsidence Control Mechanism and Effect Evaluation of Gangue-Backfilling Mining: A Case Study in China. (24th December 2018) - Li, Huaizhan; Guo, Guangli
Abstract : Comprehensive mechanization solid backfilling mining is a new technology developed in China for coal mining and surface subsidence control. Based on a gangue-backfilling project in the Yangzhuang Coal Mine, the characteristics of underlying strata and surface deformation were studied by similar-material simulation method. When the ratio of the sponge to foam was 1 : 3, the mixture can simulate well the deformation characteristics of gangues in the similar-material model. On this basis, the movement and deformation characteristics of the overlying strata caused by gangue-backfilling mining were studied. The findings indicate that compared with caving mining, the expansion coefficient of overlying strata, the interlayer fracture, and the subsidence value were smaller in backfilling mining, with the integral overlying strata subsidence occurring. Meanwhile, the reduction ratio of surface subsidence after backfilling mining was more than 85%, verified by the subsidence-monitoring results. The research outcomes in this paper have significance for coal resource exploitation of similar mines around the world.